Identification of Sediment Formation Based on Magnetic Content and Element Composition of Mud Volcano in Sangiran Sediment using VSM and X-Ray Fluorescence - Hapsoro, Cahyo Aji; Mariyanto, Mariyanto; Agustine, Eleonora; Iryanti, Mimin; Indriana, Rina Dwi; Rifai, Mochamad Khoirul; Ibrahim, Alpan; Budiono, Kharisma Asmarani (Universitas Negeri Malang, 2023)
Based on trace geological history and several studies, the Sangiran mud volcano provides insight into the geology and hydrology of the region, aquifer system in the basin, groundwater flow patterns and characteristics, rock lithology, hydrogeology condition, and saltwater trap mapping. Related to these conditions, studies were conducted on the magnetic content and composition of the major oxide compounds in the Sangiran sediments. Sample analysis was based on geochemical methods. The methods consist of frequency dependent magnetic susceptibility and vibrating sample magnetometer (VSM) analysis. Geochemical analyses using x-ray fluorescence (XRF) analysis have been conducted and various elemental grades have been determined. VSM results confirm that the magnetic content of Sangiran sediments is partly dominated by Fe (17.66 percent) contained in hematite (Fe2O3). At the same time, the samples of Sangiran sediment were enriched by Si, Fe, Al, Ca, Cl, Ti, and K according to XRF measurements. The samples exhibited the highest Si and Fe concentrations in samples T1 (Si is 29.48 percent and Fe is 13.66 percent) and T7 (Si is 24.95 percent and Fe is 12.01 percent). Meanwhile, in the T4 sample, the highest concentrations were Si and Ca, 23.45 percent and 13.45 percent, respectively. Retrieved from the magnetic susceptibility measurement, this paper confirm that Fe content is one of the components of volcanic ash in the Sangiran sediment.DOI: 10.17977/um024v8i12023p009